Comparison of Ringer’s Lactate Versus 0.9% Normal Saline Solution in the Management of Diabetic Ketoacidosis - Jahan Sardar, Abdul Baqi, Muhammad Nadeem, Medrarullah Khan, Kalim Ullah Khan, Sobiya Mohiuddin Omar, Naheed Mumtaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetic ketoacidosis (DKA) is a life-threatening diabetic condition characterized by metabolic and homeostatic disturbances. KDA is a common condition in people with diabetes, especially in children and adolescents Objective: To compare ringer’s lactate versus 0.9% normal saline solution in the management of diabetic ketoacidosis Methodology: The study design was randomized control trial carried out at the Medical ‘A’ ward Khyber teaching hospital (KTH) Peshawar for a period of six months after synopsis approval. Patients were divided into two groups, groups A, receive 0.9% normal saline infusion and group B receive ringers lactate infusion. 82 subjects were included in each group. SPSS software version 20 was used for analyzing data. Results: In group B subjects, the serum bicarbonates level was higher than group A subjects (p=0.091). The Anion gap and blood PH level increases non-significantly in both the groups over a period of time (p=0.061). The mean hospital stay in group A and group B was 13.11 hours and 11.5 hours respectively (p=0.0031). The fluid quantity required in group A was more than group B (p=0.0031) Conclusion: When prescribing fluid, clinicians should always be cautious since any fluid may be dangerous if dosed wrongly. The ringer’s lactate was shown to be superior to 0.9 % normal saline in terms of alleviating DKA quicker in our study.